High-frequency oscillations-based precise temporal resolution of short latency afferent inhibition in the human brain - Motolese, Francesco; Rossi, Mariagrazia; Capone, Fioravante; Cruciani, Alessandro; Musumeci, Gabriella; Manzo, Marco; Pilato, Fabio; Di Pino, Giovanni; Di Lazzaro, Vincenzo (Clinical neurophysiology, 2022)
•Sensorimotor integration can be explored through a conditioned transcranial magnetic stimulation (TMS) protocol -i.e., short-latency afferent inhibition (SAI).•Coupling peripheral and cortical stimulation at early interstimulus intervals may modulate muscle response.•Afferent inhibition is produced both through a direct (thalamus-motor cortex) and indirect (thalamus-somatosensory-motor cortex) pathway. Sensorimotor integration is a crucial process for adaptive behaviour and can be explored non-invasively with a conditioned transcranial magnetic stimulation (TMS) paradigm - i.e. short-latency afferent inhibition (SAI). To gain insight into the sensorimotor integration phenomenon, we used two different approaches to combine peripheral and cortical stimulation in the SAI paradigm, measuring not only the latency of low frequency somatosensory evoked potentials (SEPs) but also the peaks of high frequency oscillations (HFOs) underlying SEPs. The interstimulus intervals (ISIs) between the electrical stimulation of the median nerve and the motor cortex magnetic stimulation were determined relative to the latency of the earliest SEPs cortical potential (N20) or the HFOs peaks. In particular, the first and last negative and positive peaks of HFOs were extracted through a custom-made MATLAB script. Thirty-three healthy subjects participated in this study. We found out that muscle responses after TMS were suppressed when ISIs were comprised between –1 to +3 ms relative to the N20 peak and at all ISIs relative to HFOs peaks, except for the first negative peak. Coupling peripheral and cortical stimulation at early interstimulus intervals – before the SEPs N20 peak - may modulate muscle response. Our findings confirm that afferent inhibition is produced both through a direct (thalamus-motor cortex) and indirect (thalamus-somatosensory-motor cortex) pathway.